Dynamic Transcriptomic Profiling During Liver Development in Schizothorax Prenanti - Ni, Jiahui; Zhu, Peng; Mo, Qilang; Luo, Wei; Du, Zongjun; Jiang, Jun; Yang, Song; Zhao, Liulan; Gong, Quan; Wang, Yan (Frontiers in Physiology, 2022)
Abstract Liver is an important organ for glucose and lipid metabolism, immunity, and detoxification in fish. However, the gene regulatory network of postnatal liver development still remains unknown in teleost fish. In this study, we performed transcriptome analysis on the liver of S.prenanti at three stages. A total of 1692 differentially expressed genes (DGEs) were identified across three liver developmental stages. The oil red O staining and PAS staining revealed that the lipid content of liver was increased and the glycogen content of liver was decreased during liver development. The fatty acids biosynthesis related genes were upregulated in adult and young stages compared with juvenile stage, while lipid degradation related genes were downregulated. The genes related to glycolysis, gluconeogenesis and glycogenolysis were upregulated in juvenile or young stages compared with adult stage. Further pathway analysis indicated that the CYP450 pathway, cell cycle and amino acid metabolic pathway were induced in the process of liver maturation. Our study presents the gene expression pattern in different liver development stages of S. prenanti and may guide future studies on metabolism of S. prenanti liver.